The Radvilas as Grand Masters of the Hunt of the Grand Duchy of Lithuania: Officials and the Ruler’s Best Friends - Zarankaitė, Toma (Senoji Lietuvos literatūra, 2015)
In the sixteenth century, the hunts held by the grand duke of Lithuania, which in their significance in the Grand Duchy of Lithuania superseded the economic aspect, were one of the opportunities of consolidation of the grand duke’s court and his environment as well as a perfect occasion to start and maintain close contacts with the ruler. A passion for hunting and friendship united Mikalojus Radvila Rudasis (Mikolaj Radziwill the Red), the grand master of the hunt of the Grand Duchy of Lithuania (ловчий великий in Ruthenian, łowczy hospodarski, łowczy wielki in Polish, praefectus venationum in Latin, Oberjagermeister in German) and the ruler Žygimantas Augustas (Sigismund Augustus). Such a relationship evolved not only during the time spent together in the hunt, but also during the organization of hunts. The grand master of the hunt accompanied the ruler throughout the whole duration of the hunt and therefore often travelled with him. The emergence of this office alleviated the efforts of the ruler to restrict wilful destruction of forests and hunting areas, because grand masters of the hunt were put in charge of all forests owned by the ruler of the Grand Duchy of Lithuania. Appointing Mikalojus Radvila Rudasis to this office signified appreciation of his hunting skills and was an initial stage in his career that influenced his subsequent relationships with the ruler; it granted him exclusive hunting rights which not only demonstrated the ruler’s favour and friendship, but also yielded tangible economic gain. The actual load of the organization of the hunt was borne by the masters of the hunt (ловчий in Ruthenian, łowczy in Polish, venator in Latin), who were hierarchically subordinated to the grand master of the hunt. Being next to the ruler, the grand master of the hunt of the Grand Duchy of Lithuania occupied the position of the hunting companion, while in the process of organization he would assume responsibility for the coordination of preparatory actions and for social aspects of the hunt. The established duties and functions of grand masters of the hunt of the Grand Duchy of Lithuania did not change up until the end of the sixteenth century, and the significance of this office did not lose any of its importance. After the death of Mikalojus Radvila Rudasis, whose relationship with the ruler was primarily based on a friendly emotional connection intertwined with the official duties of the grand master of hunt of the Grand Duchy of Lithuania, this office remained in the hands of important families of the Grand Duchy: the Valavičius, the Naruševičius, the Radvila, and others who ‘inherited’ it from their next of kin.
Keywords: -